Design and Selection of The Face Shield Materials as a Self-Protective Tool in Preventing COVID-19 using The Analytical Hierarchy Process Method - Marcy L Pattiapon (UNIPA PRESS, 2021)
The world has been shocked by the emergence of COVID-19 since December 2019 which is an acute respiratory disease caused by a corona virus called severe acute respiratory syndrome coronavirus 2 or abbreviated as SARSCoV-2 (Gorbalenya et al., 2020). As of June 17, 2020, the World Health Organization (WHO) noted that there were 8,061,550 people infected with COVID-19 and 440,290 people died (WHO, 2020a). Even though the Case Fatality Rate (CFR) of COVID-19 is only around 5.46%, this disease is very dangerous because of its spread so fast it has infected 216 countries (Worldometer, 2020). To prevent uncontrolled spread, WHO declared COVID-19 a pandemic on March 11, 2020 (WHO, 2020b) to increase awareness of this disease. The status of this pandemic is a concern for the world to make various efforts to prevent the spread of COVID-19. One way to protect yourself from spreading COVID-19 is to use Personal Protective Equipment. Face shield is a personal protective device that functions to protect the face from exposure to dangerous substances in the case of the spread of the Covid-19 virus. A good face shield is a face shield that has a high level of durability, has high material quality, has a sufficient level of elasticity, and the costs incurred are not too expensive.In choosing the best alternative in making a decision, the right method is needed so that the best alternative is obtained from various predetermined criteria.Then the Analytical Hierarchy Process (AHP) method is used to select the best alternative material to be used in making the Face Shield. Based on the results of the research conducted, it can be seen that each alternative has the advantage of the criteria felt by the respondent.However, of the four criteria for selecting the face shield material, the most superior or chosen as the choice is mica.Judging from the percentage of mica against the Durability criteria is 31.7%, the percentage of mica against the quality criteria is 43.1%.